Vines in Florida Citrus - Stephen H. Futch (EDIS)
HS-1063, a 3-page illustrated fact sheet by Stephen H. Futch, provides growers with detection and management information for vine weeds in citrus groves. Includes a table of herbicides recommended for vine control. Published by the UF Department of Horticultural Sciences, June 2007.